Short term hearing results in patients with otosclerosis after stapedotomy in a tertiary care center. - Rayamajhi , P; Rauniyar , N (Journal of Institute of Medicine Nepal, 2018)
Introduction: Stapedotomy done for otosclerosis is one of the finest middle ear surgery and needs great expertise. The present study is done to evaluate the short-term hearing results in patients with otosclerosis and treated with primary stapedotomy. Methods: A retrospective chart review of patients after stapedotomy surgery was done from April 2011 to October 2016. Stapedotomy was performed under local anesthesia using a Teflon piston under local anesthesia. The patients were followed up after 6 weeks for the assessment of the hearing status. The hearing assessment was done using the Air Bone gap improvement and Air Bone gap closure (AB gap closure) pre and postoperatively. Results: Total of 73 cases were retrieved from hospital database. 3 cases were excluded and analysis of only 70 cases was done. Among the total patients 85.71% of the patients had bilateral involvement of the disease. The overall mean pre-operative pure tone Air conduction average was 55.66 dB, SD 11.576 (95% CI; 52.57-59212), while the overall mean post -operative pure tone average was 17.63 dB, SD 11.958 (95% CI; 14.70-21.57). This difference was found to be statistically significant (p = 0.000). The overall mean pre-operative air bone gap was 37.65 dB and the overall mean post -operative air bone gap was 18.47dB. This difference was found to be statistically significant (p = 0.000). Conclusion: This study confirms that stapedotomy for clinical otosclerosis is a safe and successful treatment for short-term hearing improvement. Both the AC threshold and AB gap closure showed significant improvement postoperatively.